IMPLEMENTASI MANAJEMEN SYARIAH DALAM FUNGSI - FUNGSI MANAJEMEN - Sunarji Harahap (Universitas Islam Negeri Sumatera Utara, 2017)
Islam as a system of life that is perfect of course have thoughts about the concept of management. Once the importance of the field of management in terms of economic life that Islam has been set up how the actual management process, because many people assume that the narrow thinking about the true meaning of the management. Viewed from the perspective of competitors, namely the Shari'ah management industry do not consider competitors, who should be defeated or even played. But the concept is that each company is able to spur him to get better without having dropped its competitors. Competitors are partners who participated successful activities that will be implemented on the ground, and not as an opponent to be turned off. The implementation of management functions to be based on sharia Islamic values.